Trade in early India - Chakravarti, Ranabir 1953- (New Delhi : Oxford University Press, 2001)
Contributed articles.
Includes bibliographical references and index.
Keywords: Commerce, Prehistoric -- India; India -- Commerce -- History; India -- Commercial policy -- History